Variational Autoencoder를 이용한 교량 손상 위치 추정방법 - 이강혁; 정민웅; 전찬웅; 신도형; Lee, Kanghyeok; Chung, Minwoong; Jeon, Chanwoong; Shin, Do Hyoung (대한토목학회논문집, 2020)
Most deep learning (DL) approaches for bridge damage localization based on a structural health monitoring system commonly use supervised learning-based DL models. The supervised learning-based DL model requires the response data obtained from sensors on the bridge and also the label which indicates the damaged state of the bridge. However, it is impractical to accurately obtain the label data in fields, thus, the supervised learning-based DL model has a limitation in that it is not easily applicable in practice. On the other hand, an unsupervised learning-based DL model has the merit of being able to train without label data. Considering this advantage, this study aims to propose and theoretically validate a damage localization approach for bridges using a variational autoencoder, a representative unsupervised learning-based DL network: as a result, this study indicated the feasibility of VAE for damage localization. 구조물 건전도 모니터링 시스템을 기반하는 교량 딥러닝 손상 추정 기법들은 대부분 지도학습을 기반으로 하고 있다. 지도학습의 특성상 손상 위치 추정 딥러닝 모델의 학습을 위해 교량의 손상 위치를 나타내는 라벨(Label) 데이터와 이에 따른 교량의 거동 데이터가 필요하다. 하지만 실제 현장에서 손상 위치 라벨 데이터를 정확히 얻어내는 것은 매우 어려운 일이므로, 지도학습 기반 딥러닝은 현장 적용성이 떨어진다는 한계가 있다. 반면에, 비지도학습 기반 딥러닝은 이러한 라벨 데이터 없이도 학습이 가능하다는 장점이 있다. 이러한 점에 착안하여 본 연구에서는 비지도 학습의 대표적인 딥러닝 기법인 Variational Autoencoder를 활용한 교량 손상 위치 추정의 방법을 제안하고 검증하였으며, 그 결과, 교량 손상 위치 추정을 위한 VAE의 적용 가능성을 보였다.